Markets Take Breaks: Dynamic Price Competition with Opening Hours - Steffen Eibelshäuser; Sascha Wilhelm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study price cycles in the German retail gasoline market. We extend existing models of Bertrand competition by product differentiation, firm size and business hours. With sufficiently low product differentiation, there exists a unique subgame perfect equilibrium featuring Edgeworth price cycles. We test the model's predictions using an extensive data set. Last, we evaluate policy interventions and show that restrictions on price setting or increased market transparency harm consumer welfare.
Keywords: D43; L11; L13; L81; 330